ILMU KALAM DALAM PEMBACAAN KONTEMPORER - Farichah Farichah (IAIN Purwokerto, 2011)
The development of Islamic thought, including theology, is inseparable from its social and political setting. Political nuances in the discourse are obvious. Each group offers its own concept that is sometimes different from other groups and claims that the correct one is their own concept, while others are wrong, and this results in truth claim. All groups refer to al-Guran and Hadith as justification to support their opinions, without considering the alternative concept of truth and that the truth itself is relative. Conseguentiy, social jargons existing in the society tend to be dichotomous: Muslim — infidels, and true — false. As an Islamic thought, theology is expected to provide fresh atmosphere to create peace. For that reason, it is necessary to revise and reconstruct the old epistemology to a new epistemology. The goal is to make theology not simply an empty religious dogma, but rather a science of social critigue, which makes faith have the function of humanethics as the foundation of religion.